Growers’ perceptions in assessing the prospects, challenges and Cost-benefit analysis of agarwood (Aquilaria malaccensis roxb.) Production: A case study in Moulvibazar district of Bangladesh: Growers’ Perceptions and Profitability of Agarwood Cultivation - Hossain, Md Iqbal; Rahman, Md Abiar; Saha, Satya Ranjan; Ferdousi, Jannatul; Islam, S M Rejbanul; Haque, Md Monuwarul (Journal of the Sylhet Agricultural University, 2026)
Among the most important non-wood forest products worldwide, Agarwood, derived from Aquilaria malaccensis Roxb., has growing economic and livelihood importance along with Bangladesh. Despite its significant export potential, empirical data regarding farm-level production practices, profitability and limitations are still scarce. This present study assessed the opportunities, obstacles and cost–benefit aids of agar tree cultivation based on the perspectives of growers in Barlekha upazila, Moulvibazar district of northeastern Bangladesh. A survey was administered to 120 households between November 2019 to May 2020. Primary data were obtained using structured questionnaire surveys, focus group discussions (FGDs) and field observations. Descriptive statistics, a Constraints Facing Index (CFI) and financial evaluation instruments, such as net present value (NPV), benefit-cost ratio (BCR) and internal rate of return (IRR) were utilized for the study. The findings indicated that agar farming is primarily showed by middle aged farmers (51.67%) posing primary to secondary education, small land holdings and moderate to high production experience. Agarwood was mostly grown in mixed cropping systems within homesteads and fallow lands often in association with jackfruit, mango and acacia species reflecting significant on-farm biodiversity. The majority of famers are depended on seedlings, cultivate in nurseries and followed a traditional management technique utilizing minimal irrigation and agrochemicals. The economic analysis revealed remarkable profitability with a net return of BDT 3,300.28 per tree and a benefit cost ratio of 5.92 over a 12 years production cycle. At the hectare level the NPV was BDT 3.36 million the discounted BCR was 3.54 and the IRR was 27.45% indicating strong financial viability. However, significant barriers included inadequate finance, poor technical assistance, unavailability of enhanced varieties and restricted access to contemporary production technology. Farmers indicated that enhanced agar production needed stronger marketing channels, training, technical support, favorable government policies and access to finance facilities. The study indicates that agar tree farming is a lucrative and viable agroforestry practice in Bangladesh and certain policy and institutional interventions might significantly improve its sustainability and impact on rural life. J. Sylhet Agril. Univ. 12(2): 47-66, 2025